Self-repairing anticorrosive paint and preparation method thereof
By using a combination of cyclodextrin-based polyurethane, azophenyl composite polyurethane, hollow mesoporous silica and leveling agent in anticorrosion coatings, the lack of durability and self-repairing ability of traditional anticorrosion coatings in complex environments is solved. The problem is that the coating has high mechanical properties and effective self-repair and anti-corrosion effect are achieved.
Patent Information
- Application Number
- CN202411650060.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-19
AI Technical Summary
Traditional anticorrosion coatings perform poorly in complex environments, and lack durability and self-repair capabilities, resulting in corrosive media entering the substrate through defects, accelerating metal corrosion.
Using a self-healing anticorrosion coating, its raw material components include cyclodextrin-based polyurethane, azophenyl composite polyurethane, hollow mesoporous silica and leveling agent, self-healing mechanisms triggered by physical crosslinking and photothermal stimulation , enhance the mechanical properties and corrosion resistance of the coating.
It improves the mechanical properties, wear resistance and corrosion resistance of the coating, extends the service life of the coating, and can self-repair after damage, enhancing the anti-corrosion effect.
Smart Images

Figure BDA0005140675930000071
Abstract
Description
Technical Field
[0001] The invention relates to a self-repairing anti-corrosion coating and a preparation method thereof. Background Art
[0002] Metal corrosion is a problem that has long plagued the industrial world. It not only causes huge economic losses, but also may cause serious safety accidents and environmental pollution. According to statistics, the economic losses caused by metal corrosion in the world each year are as high as hundreds of billions of dollars, accounting for a certain proportion of the GDP of various countries. Therefore, the development of efficient anti-corrosion measures is of great significance to protect metal structures, extend equipment life, and ensure production safety. Among the many anti-corrosion measures, coating anti-corrosion has become one of the most commonly used methods due to its convenient construction, low cost, and wide range of applications.
[0003] Although the coating anti-corrosion technology is quite mature, traditional anti-corrosion coatings still have some shortcomings, especially in terms of durability and self-healing ability in complex environments. Once scratches or cracks appear on the coating, the corrosive medium will penetrate the substrate through these defects, accelerate the metal corrosion process, and cause anti-corrosion failure. Therefore, the research and development of anti-corrosion coatings with self-healing functions has become an important direction in recent years.
[0004] Polyaniline is an excellent green anti-corrosion inhibitor. Compared with conventional corrosion inhibitors, it has no environmental side effects and exhibits "activation-passivation" behavior on metal materials, that is, it accelerates the formation of a passivation film on the metal surface through a reversible redox reaction, thereby effectively inhibiting the occurrence of corrosion reactions. The introduction of polyaniline into azophenyl composite polyurethane can effectively improve the anti-corrosion performance of azophenyl composite polyurethane. However, polyaniline has poor compatibility with coating matrices (such as epoxy resins, acrylic resins, etc.), which leads to poor dispersibility in coatings, thereby affecting the overall performance of the coating. Specifically, it manifests itself in problems such as decreased adhesion of the coating, weakened mechanical strength, and unstable anti-corrosion effect.
[0005] In order to overcome the above-mentioned difficulties, the present invention proposes a self-repairing anti-corrosion coating and a preparation method thereof. Summary of the invention
[0006] The purpose of the present invention is to provide a self-repairing anti-corrosion coating and a preparation method thereof to solve the technical problems mentioned in the above background technology.
[0007] The technical solution for achieving the purpose of the present invention is: a self-repairing anti-corrosion coating, wherein the raw material components include, by weight, 1.5 to 2.5 parts by weight of cyclodextrin-based polyurethane, 1.5 to 2.5 parts by weight of azophenyl composite polyurethane, 0.15 to 0.25 parts by weight of hollow mesoporous silica, 0.15 to 0.25 parts by weight of a leveling agent, and 7.5 to 12.5 parts by weight of a solvent.
[0008] Furthermore, the cyclodextrin-based polyurethane is obtained by reacting cyclodextrin with toluene diisocyanate.
[0009] Furthermore, the azophenyl composite polyurethane is obtained by a composite reaction of polytetrahydrofuran, 4,4'-dihydroxyazobenzene, modified polyaniline and toluene diisocyanate.
[0010] Furthermore, the modified polyaniline is obtained by modifying polyaniline with cystine.
[0011] The present invention also provides a method for preparing a self-repairing anti-corrosion coating, comprising the following preparation steps:
[0012] 1.5-2.5 parts by mass of cyclodextrin-based polyurethane and 1.5-2.5 parts by mass of azophenyl composite polyurethane are dissolved in 7.5-12.5 parts by mass of dimethyl sulfoxide solvent, and then 0.15-0.25 parts by mass of hollow mesoporous silica are added, and dispersed at 2000-4000 rpm for 25-35 minutes, and then 0.15-0.25 parts by mass of leveling agent are added, and dispersion is continued for 4-6 minutes, and treated with 365nm UV for 10-20 minutes, and then dried in an oven at 58-62°C for 28-32 minutes to obtain a self-repairing anti-corrosion coating.
[0013] Furthermore, the preparation steps of the cyclodextrin-based polyurethane are as follows: 1.5 to 2.5 parts by mass of polytetrahydrofuran and 0.8 to 1.2 parts by mass of toluene diisocyanate are dissolved in 9 to 11 parts by mass of dimethyl sulfoxide, and then 2 to 2.4 parts by mass of 0.09 to 0.11 g / mL of cyclodextrin in dimethyl sulfoxide solution are added, and after mixing evenly, the mixture is reacted in a water bath at 48 to 52° C. for 50 to 70 minutes, and then cured in an oven at 58 to 62° C. for 28 to 32 minutes to obtain a cyclodextrin-based polyurethane.
[0014] Furthermore, the preparation steps of the azophenyl composite polyurethane are as follows: 19 to 21 parts by mass of polytetrahydrofuran, 0.09 to 0.11 parts by mass of 4,4'-dihydroxyazobenzene, 0.18 to 0.22 parts by mass of modified polyaniline, and 9 to 11 parts by mass of dimethyl sulfoxide are stirred and mixed to obtain a mixed solution A; 0.9 to 1.1 parts by mass of toluene diisocyanate and 0.018 to 0.022 parts by mass of dibutyltin dilaurate are poured into solution A, reacted in a water bath at 49 to 51°C for 55 to 65 minutes, and cured in an oven at 60°C for 28 to 32 minutes to synthesize azophenyl polyurethane.
[0015] Furthermore, the preparation steps of the modified polyaniline are as follows: 3 parts by mass of polyaniline are dispersed in 500 parts by mass of deionized water, and then 27 to 33 parts by mass of cysteine are added for mixing, followed by 25 to 35 minutes of ultrasonic assisted dispersion, magnetic stirring for reaction for 23 to 25 hours, filtering and repeatedly washing with deionized water and ethanol for 2 to 4 times, and finally drying at room temperature for 12 hours to obtain the modified polyaniline.
[0016] Furthermore, the self-repairing method of the self-repairing anti-corrosion coating is to 2 , irradiate with 405nm laser for 20 to 30s.
[0017] By adopting the above technical solution, the present invention has the following beneficial effects:
[0018] The raw material components of the self-repairing anti-corrosion coating of the present invention include cyclodextrin-based polyurethane, azophenyl composite polyurethane, hollow mesoporous silica, and a leveling agent; wherein the cyclodextrin-based polyurethane is obtained by reacting cyclodextrin with toluene diisocyanate; and the azophenyl composite polyurethane is obtained by a composite reaction of polytetrahydrofuran, 4'-dihydroxyazobenzene, modified polyaniline, and toluene diisocyanate.
[0019] Polyaniline is an excellent green corrosion inhibitor. Compared with conventional corrosion inhibitors, it has no environmental side effects and exhibits "activation-passivation" behavior on metal materials, that is, it accelerates the formation of a passivation film on the metal surface through a reversible redox reaction, thereby effectively inhibiting the occurrence of corrosion reactions. The introduction of polyaniline into azophenyl composite polyurethane can effectively improve the anti-corrosion properties of azophenyl composite polyurethane. However, polyaniline is easy to agglomerate in the resin matrix, which is not conducive to its uniform dispersion and will reduce the adhesion of the coating. The use of cysteine to modify polyaniline can effectively improve the compatibility of polyaniline in azophenyl composite polyurethane.
[0020] Secondly, cyclodextrin-based polyurethane, azophenyl composite polyurethane, hollow mesoporous silica and leveling agent are mixed to prepare anti-corrosion coating. The polymer chains of cyclodextrin-based polyurethane and azophenyl composite polyurethane penetrate into the pores of hollow mesoporous silica, and physical cross-linking is carried out with hollow mesoporous silica as the physical cross-linking point, thereby increasing the cross-linking density of the self-healing anti-corrosion coating, thereby increasing the mechanical properties, wear resistance and anti-corrosion properties of the self-healing anti-corrosion coating. At the same time, hollow mesoporous silica also provides an additional physical barrier. When the coating is damaged externally, the hollow mesoporous silica can effectively prevent the further expansion of the damaged surface and prevent the corrosive medium from invading the substrate through cracks or scratches. This extends the service life of the coating and improves its anti-corrosion effect; when subjected to photothermal stimulation, cis-azobenzene will be converted into trans-azobenzene and combine with cyclodextrin, which will cause the polymer chains of the coating to shrink, triggering the contraction of cyclodextrin-based polyurethane and azophenyl composite polyurethane interspersed in the hollow mesoporous silica. With the hollow mesoporous silica as the physical fixed point, the polymer layers on both sides of the damaged area are accurately pulled inward, causing the damaged surfaces to approach each other until they come into contact. Once in contact, the trans-azobenzene on the damaged surface will continue to react with cyclodextrin, and at the same time, azobenzene and polyaniline will convert the absorbed light energy into heat energy, activating the recombination of disulfide bonds at the damaged site, thereby completing the self-repair process. DETAILED DESCRIPTION
[0021] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0022] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.
[0023] The raw materials of some embodiments and comparative examples of the present invention are as follows:
[0024] The solvent used was dimethyl sulfoxide;
[0025] The cyclodextrin used is α-cyclodextrin;
[0026] The leveling agent used is BYK-333 from BYK Chemical Company;
[0027] Polytetrahydrofuran (average relative molecular mass about 1000);
[0028] Polyaniline: The average relative molecular mass is about 15,000.
[0029] The preparation steps of hollow mesoporous silica are as follows: add 0.2 parts by mass of hexadecyltrimethylammonium bromide to 200 parts by mass of a mixed solution with an alcohol-water ratio of 4 to 9:1, and drop 2 mol / L NaOH solution until the pH is 9, then add 2 parts by mass of paraffin, use a homogenizer to emulsify at a speed of 5000 r / min for 5 minutes, then drop 2 parts by mass of ethyl orthosilicate, react for 2 hours under the conditions of 80°C and 400 r / min stirring, filter the product after the reaction, wash it with deionized water and anhydrous ethanol for 2 to 4 times, dry it, and calcine it at 600°C for 3 hours to remove the liquid paraffin template and surfactant, so as to obtain hollow mesoporous silica with a specific surface area of 802.7263 m 2 / g, pore volume 0.89cm 3 / g, and the average pore size is 4.19nm.
[0030] (Example 1)
[0031] A method for preparing a self-repairing anti-corrosion coating comprises the following preparation steps:
[0032] 1.5 parts by mass of cyclodextrin-based polyurethane and 1.5 parts by mass of azophenyl composite polyurethane were dissolved in 7.5 parts by mass of solvent dimethyl sulfoxide, and then 0.15 parts by mass of hollow mesoporous silica was added and dispersed at 2000 rpm for 25 minutes. Then 0.15 parts by mass of leveling agent was added and dispersed for another 4 minutes. The mixture was treated with 365 nm UV for 10 minutes and then dried in an oven at 58°C for 28 minutes to obtain a self-repairing anti-corrosion coating.
[0033] The preparation steps of the cyclodextrin-based polyurethane are as follows: 1.5 parts by mass of polytetrahydrofuran and 0.8 parts by mass of toluene diisocyanate are dissolved in 9 parts by mass of dimethyl sulfoxide, and then 2 parts by mass of 0.09 g / mL dimethyl sulfoxide solution of cyclodextrin are added, and after mixing evenly, the mixture is reacted in a 48° C. water bath for 50 minutes, and then cured in an oven at 58° C. for 28 minutes to obtain the cyclodextrin-based polyurethane.
[0034] The preparation steps of the azophenyl composite polyurethane are as follows: 19 parts by mass of polytetrahydrofuran, 0.09 parts by mass of 4,4'-dihydroxyazobenzene, 0.18 parts by mass of modified polyaniline and 9 parts by mass of dimethyl sulfoxide are stirred and mixed to obtain a mixed solution A; 0.9 parts by mass of toluene diisocyanate and 0.018 parts by mass of dibutyltin dilaurate are poured into solution A, reacted in a 49° C. water bath for 55 minutes, and cured in a 60° C. oven for 28 minutes to synthesize the azophenyl polyurethane.
[0035] The preparation steps of the modified polyaniline are as follows: 3 parts by mass of polyaniline are dispersed in 500 parts by mass of deionized water, and then 27 parts by mass of cysteine are added for mixing, followed by 25 minutes of ultrasonic-assisted dispersion, magnetic stirring for reaction for 23 hours, filtering and repeatedly washing with deionized water and ethanol twice, and finally drying at room temperature for 12 hours to obtain the modified polyaniline.
[0036] (Example 2)
[0037] A method for preparing a self-repairing anti-corrosion coating comprises the following preparation steps:
[0038] 2 parts by mass of cyclodextrin-based polyurethane and 2 parts by mass of azophenyl composite polyurethane were dissolved in 10 parts by mass of solvent dimethyl sulfoxide, and then 0.2 parts by mass of hollow mesoporous silica was added and dispersed at 3000 rpm for 30 minutes. Then 0.2 parts by mass of leveling agent was added and dispersed for 5 minutes. The mixture was treated with 365 nm UV for 15 minutes and then dried in an oven at 60°C for 30 minutes to obtain a self-repairing anti-corrosion coating.
[0039] The preparation steps of the cyclodextrin-based polyurethane are as follows: 2 parts by mass of polytetrahydrofuran and 1 part by mass of toluene diisocyanate are dissolved in 10 parts by mass of dimethyl sulfoxide, and then 2.2 parts by mass of 0.1 g / mL dimethyl sulfoxide solution of cyclodextrin is added, and after mixing evenly, the mixture is reacted in a 50° C. water bath for 60 minutes, and then cured in an oven at 60° C. for 30 minutes to obtain the cyclodextrin-based polyurethane.
[0040] The preparation steps of the azophenyl composite polyurethane are as follows: 20 parts by mass of polytetrahydrofuran, 0.1 parts by mass of 4,4'-dihydroxyazobenzene, 0.2 parts by mass of modified polyaniline and 10 parts by mass of dimethyl sulfoxide are stirred and mixed to obtain a mixed solution A; 1 part by mass of toluene diisocyanate and 0.02 parts by mass of dibutyltin dilaurate are poured into solution A, reacted in a 50°C water bath for 60 minutes, and cured in a 60°C oven for 30 minutes to synthesize the azophenyl polyurethane.
[0041] The preparation steps of the modified polyaniline are as follows: 3 parts by mass of polyaniline are dispersed in 500 parts by mass of deionized water, 30 parts by mass of cysteine are added and mixed, and then ultrasonic-assisted dispersion is performed for 30 minutes, magnetic stirring is performed for reaction for 24 hours, filtering and repeatedly washing with deionized water and ethanol for 3 times, and finally drying at room temperature for 12 hours to obtain the modified polyaniline.
[0042] (Example 3)
[0043] A method for preparing a self-repairing anti-corrosion coating comprises the following preparation steps:
[0044] 2.5 parts by mass of cyclodextrin-based polyurethane and 2.5 parts by mass of azophenyl composite polyurethane were dissolved in 12.5 parts by mass of solvent dimethyl sulfoxide, and then 0.25 parts by mass of hollow mesoporous silica was added and dispersed at 4000 rpm for 35 minutes. Then 0.25 parts by mass of leveling agent was added and dispersed for 6 minutes. The coating was treated with 365 nm UV for 20 minutes and then dried in an oven at 62°C for 32 minutes to obtain a self-repairing anti-corrosion coating.
[0045] The preparation steps of the cyclodextrin-based polyurethane are as follows: 2.5 parts by mass of polytetrahydrofuran and 1.2 parts by mass of toluene diisocyanate are dissolved in 11 parts by mass of dimethyl sulfoxide, and then 2.4 parts by mass of 0.11 g / mL dimethyl sulfoxide solution of cyclodextrin is added, and after mixing evenly, the mixture is reacted in a 52° C. water bath for 70 minutes, and then cured in an oven at 62° C. for 32 minutes to obtain the cyclodextrin-based polyurethane.
[0046] The preparation steps of the azophenyl composite polyurethane are as follows: 21 parts by mass of polytetrahydrofuran, 0.11 parts by mass of 4,4'-dihydroxyazobenzene, 0.22 parts by mass of modified polyaniline and 11 parts by mass of dimethyl sulfoxide are stirred and mixed to obtain a mixed solution A; 1.1 parts by mass of toluene diisocyanate and 0.022 parts by mass of dibutyltin dilaurate are poured into solution A, reacted in a 51° C. water bath for 65 minutes, and cured in a 60° C. oven for 32 minutes to synthesize the azophenyl polyurethane.
[0047] The preparation steps of the modified polyaniline are as follows: 3 parts by mass of polyaniline are dispersed in 500 parts by mass of deionized water, 33 parts by mass of cysteine are added and mixed, and then ultrasonic-assisted dispersion is performed for 35 minutes, magnetic stirring is performed for reaction for 25 hours, filtering and repeatedly washing with deionized water and ethanol for 4 times, and finally drying at room temperature for 12 hours to obtain the modified polyaniline.
[0048] Comparative Example 1
[0049] The difference between Comparative Example 1 and Example 2 is that the raw material components of the self-repairing anti-corrosion coating of Comparative Example 1 include: cyclodextrin-based polyurethane, azophenyl composite polyurethane, and leveling agent; the remaining steps and ingredients are the same as those of Example 2.
[0050] Comparative Example 2
[0051] The difference between Comparative Example 2 and Example 2 is that the raw material components of the self-repairing anti-corrosion coating of Comparative Example 1 include: azophenyl composite polyurethane, hollow mesoporous silica, and a leveling agent; the remaining steps and ingredients are the same as those of Example 2.
[0052] Comparative Example 3
[0053] The difference between Comparative Example 3 and Example 2 is that the azophenyl composite polyurethane in Comparative Example 1 is obtained by a composite reaction of polytetrahydrofuran, modified polyaniline, and toluene diisocyanate; the remaining steps and components are the same as those in Example 2.
[0054] Comparative Example 4
[0055] The difference between Comparative Example 4 and Example 2 is that the azophenyl composite polyurethane in Comparative Example 1 is obtained by the composite reaction of polytetrahydrofuran, 4,4'-dihydroxyazobenzene, polyaniline and toluene diisocyanate; the remaining steps and components are the same as those in Example 2.
[0056] Comparative Example 5
[0057] The difference between Comparative Example 5 and Example 2 is that the raw material components of the self-healing anti-corrosion coating of Comparative Example 1 include: cyclodextrin-based polyurethane, azophenyl composite polyurethane, hollow mesoporous silica, leveling agent, modified polyaniline; wherein, the azophenyl composite polyurethane is obtained by the composite reaction of 4,4'-dihydroxyazobenzene, polytetrahydrofuran, and toluene diisocyanate; the remaining steps and components are the same as those of Example 2.
[0058] Comparative Example 6
[0059] The difference between Comparative Example 6 and Example 2 is that the raw material components of the self-healing anti-corrosion coating of Comparative Example 1 include: cyclodextrin-based polyurethane, azophenyl composite polyurethane, hollow mesoporous silica, leveling agent, polyaniline; among them, it is obtained by the composite reaction of 4,4'-dihydroxyazobenzene, polytetrahydrofuran, and toluene diisocyanate; the remaining steps and ingredients are the same as Example 2.
[0060] Effect example:
[0061] Tensile properties: The tensile properties of the self-repairing anti-corrosion coatings prepared in the examples and comparative examples were tested using Shimadzu's electronic universal tensile testing machine AGS-X10KN in accordance with GB / T7762.
[0062] Anti-corrosion performance: Use a frame scraper with a gap width of 120 μm to evenly apply the self-repairing anti-corrosion coating prepared in the embodiment and the comparative example on the surface of the low carbon steel plate, and cure it in an oven at 60°C for 8 hours to obtain a self-repairing anti-corrosion coating. The salt spray resistance of the self-repairing anti-corrosion coating is tested according to GB / T1771.
[0063] Self-repairing performance: The mechanical self-repairing properties of the self-repairing anti-corrosion coatings prepared in the examples and comparative examples were tested using Shimadzu's electronic universal tensile testing machine AGS-X10KN in accordance with GB / T7762. The tensile rate was 200 mm / min, and the samples were cut into dumbbells with a width of 4 mm, a length of 50 mm, and a thickness of 2 mm, with a spacing of 20 mm between the two ends. The self-repairing efficiency of the coating was evaluated by measuring the mechanical properties of the uncut coating and the cut-repaired coating. The self-repairing efficiency of the coating (η) was calculated according to formula (1). The cut-repaired coating is the self-repairing anti-corrosion coating after cutting at 100 mW / cm 2 , irradiated with 405nm laser for 20s;
[0064] η=ε healing / ε initial × 100% Formula (1)
[0065] Where: ε initial —Elongation at break of uncut coating; ε healing —Elongation at break of the repaired coating.
[0066] Adhesion: Use a frame scraper with a gap width of 120 μm to evenly apply the self-repairing anti-corrosion coating prepared in the embodiment and the comparative example on the surface of the low carbon steel plate, and cure it in an oven at 60°C for 8 hours to obtain a self-repairing anti-corrosion coating. The adhesion of the self-repairing anti-corrosion coating is tested according to GB / T9286.
[0067] Table 1 below shows the performance test results of the self-repairing anti-corrosion coatings prepared in Examples and Comparative Examples:
[0068] Table 1
[0069]
[0070] It can be seen from Table 1 above that the self-repairing anti-corrosion coatings prepared in Examples 1 to 3 have good tensile properties, anti-corrosion properties, self-repairing properties and adhesion.
[0071] Compared with Example 2, the raw material components of the self-healing anti-corrosion coating in Example 1 do not contain hollow mesoporous silica, and cannot provide physical cross-linking points for physical cross-linking. When subjected to photothermal stimulation, cis-azobenzene is converted into trans-azobenzene and combined with cyclodextrin, thereby causing the polymer chains of the coating to shrink. Without hollow mesoporous silica as a physical fixed point, an inward pulling force is accurately applied to the polymer layers on both sides of the damaged area, causing the damaged surfaces to approach each other until they are in contact. The tensile strength and self-healing performance of the coating obtained in Example 2 are better.
[0072] Compared with Example 2, Comparative Example 2 does not add cyclodextrin-based polyurethane to the raw material components of the self-healing anti-corrosion coating in Comparative Example 2. When subjected to photothermal stimulation, cis-azobenzene is converted into trans-azobenzene, and the polymer chains of the coating cannot shrink, resulting in poor self-healing performance.
[0073] Comparative Example 3 is compared with Example 2. In Comparative Example 3, the azophenyl composite polyurethane is not added with 4,4'-dihydroxyazobenzene. When subjected to light and heat stimulation, the polymer chain cannot shrink, and the tensile performance and self-repairing performance are poor.
[0074] Compared with Example 2, Comparative Example 4 does not modify the polyaniline. The polyaniline is easy to agglomerate in the resin matrix, and the adhesion is reduced, the tensile properties and corrosion resistance are poor, and the self-healing effect is poor. This is because the polyaniline is unevenly distributed, resulting in uneven self-healing effects in different parts of the coating.
[0075] Comparative Example 5 is compared with Example 2. In Comparative Example 5, the raw material of the self-repairing anti-corrosion coating is not modified polyaniline to prepare azophenyl composite polyurethane, but is directly mixed with cyclodextrin-based polyurethane, azophenyl composite polyurethane, hollow mesoporous silica, and leveling agent to prepare the self-repairing anti-corrosion coating. The tensile properties, anti-corrosion properties, self-repairing properties, and adhesion are relatively weak. It may be that the self-repairing anti-corrosion coating directly prepared by modified polyaniline has better compatibility than preparing azophenyl composite polyurethane first.
[0076] The difference between Comparative Example 6 and Comparative Example 5 is that the polyaniline is not modified in Comparative Example 6, and the polyaniline is easy to agglomerate in the resin matrix, resulting in reduced adhesion, poor tensile properties, and poor corrosion resistance. The self-healing effect is poor because the polyaniline is unevenly distributed, resulting in uneven self-healing effects in different parts of the coating.
[0077] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A self-repairing anti-corrosion coating, characterized in that: In parts by weight, the raw material components include 1.5 to 2.5 parts by weight of cyclodextrin-based polyurethane, 1.5 to 2.5 parts by weight of azophenyl composite polyurethane, 0.15 to 0.25 parts by weight of hollow mesoporous silica, 0.15 to 0.25 parts by weight of a leveling agent, and 7.5 to 12.5 parts by weight of a solvent.
2. The self-repairing anti-corrosion coating according to claim 1, characterized in that: The cyclodextrin-based polyurethane is obtained by reacting cyclodextrin with toluene diisocyanate.
3. The self-repairing anti-corrosion coating according to claim 1, characterized in that: The azophenyl composite polyurethane is obtained by composite reaction of polytetrahydrofuran, 4,4'-dihydroxyazobenzene, modified polyaniline and toluene diisocyanate.
4. The self-repairing anti-corrosion coating according to claim 3, characterized in that: The modified polyaniline is obtained by modifying polyaniline with cystine.
5. A method for preparing a self-repairing anti-corrosion coating, characterized in that: The method comprises the following preparation steps: 1.5-2.5 parts by mass of cyclodextrin-based polyurethane and 1.5-2.5 parts by mass of azophenyl composite polyurethane are dissolved in 7.5-12.5 parts by mass of dimethyl sulfoxide solvent, and then 0.15-0.25 parts by mass of hollow mesoporous silica are added, and dispersed at 2000-4000 rpm for 25-35 minutes, and then 0.15-0.25 parts by mass of leveling agent are added, and dispersion is continued for 4-6 minutes, and treated with 365nm UV for 10-20 minutes, and then dried in an oven at 58-62°C for 28-32 minutes to obtain a self-repairing anti-corrosion coating.
6. The method for preparing the self-repairing anti-corrosion coating according to claim 5, characterized in that: The preparation steps of the cyclodextrin-based polyurethane are as follows: 1.5 to 2.5 parts by mass of polytetrahydrofuran and 0.8 to 1.2 parts by mass of toluene diisocyanate are dissolved in 9 to 11 parts by mass of dimethyl sulfoxide, and then 2 to 2.4 parts by mass of a 0.09 to 0.11 g / mL dimethyl sulfoxide solution of cyclodextrin is added, and after uniform mixing, the mixture is reacted in a water bath at 48 to 52° C. for 50 to 70 minutes, and then cured in an oven at 58 to 62° C. for 28 to 32 minutes to obtain the cyclodextrin-based polyurethane.
7. The method for preparing the self-repairing anti-corrosion coating according to claim 5, characterized in that: The preparation steps of the azophenyl composite polyurethane are as follows: 19 to 21 parts by weight of polytetrahydrofuran, 0.09 to 0.11 parts by weight of 4,4'-dihydroxyazobenzene, 0.18 to 0.22 parts by weight of modified polyaniline, and 9 to 11 parts by weight of dimethyl sulfoxide are stirred and mixed to obtain a mixed solution A; 0.9 to 1.1 parts by weight of toluene diisocyanate and 0.018 to 0.022 parts by weight of dibutyltin dilaurate are poured into the solution A, reacted in a water bath at 49 to 51° C. for 55 to 65 minutes, and cured in an oven at 60° C. for 28 to 32 minutes to synthesize the azophenyl polyurethane.
8. The method for preparing the self-repairing anti-corrosion coating according to claim 5, characterized in that: The preparation steps of the modified polyaniline are as follows: 3 parts by mass of polyaniline are dispersed in 500 parts by mass of deionized water, and then 27 to 33 parts by mass of cysteine are added for mixing, followed by 25 to 35 minutes of ultrasonic assisted dispersion, magnetic stirring for reaction for 23 to 25 hours, filtering and repeatedly washing with deionized water and ethanol for 2 to 4 times, and finally drying at room temperature for 12 hours to obtain the modified polyaniline.
9. The method for preparing the self-repairing anti-corrosion coating according to any one of claims 5 to 8, characterized in that: The self-repairing method of the self-repairing anti-corrosion coating is to 2 , irradiate with 405nm laser for 20 to 30s.
Citation Information
Patent Citations
Method for preparing light-response variable hydrophobic polyurethane
CN106750090A
Aluminum alloy surface coating with autonomous and non-autonomous repair functions
CN111662617A
Self-repairing waterborne polyurethane anticorrosive coating and preparation method thereof
CN113831825A
Self-healing and Bacteria Resistant Coating Materials for Various Substrates
US20180057706A1
Cited By
Self-repairing type polyurea protective coating and preparation method thereof
CN121108853A